2014
DOI: 10.2527/jas.2014-8000
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of urinary and fecal nitrogen excretion by beef cattle1

Abstract: An analysis of predicting urinary and fecal N excretion from beef cattle was conducted using a data set summarizing 49 published studies representing 180 treatment means for 869 animals. Variables included in the data set were initial BW (kg), DMI (kg/d), dietary CP content (% of DM), N intake (g/d), apparent total tract N digestibility (%), and urinary and fecal N excretion (g/d). Correlation analysis examined relationships between animal and dietary variables and N excretion. A mixed model regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 74 publications
(84 reference statements)
7
51
0
10
Order By: Relevance
“…Predictions of N excretion proposed by Waldrip et al (2013) and Dong et al (2014), and used by BCNRM (2016), also showed a positive correlation between nitrogen intake and excretion. These authors observed better fit of the prediction equations using the N intake than the percentage of crude protein in the diet, and the same behavior was observed in the present database.…”
Section: No3mentioning
confidence: 76%
See 3 more Smart Citations
“…Predictions of N excretion proposed by Waldrip et al (2013) and Dong et al (2014), and used by BCNRM (2016), also showed a positive correlation between nitrogen intake and excretion. These authors observed better fit of the prediction equations using the N intake than the percentage of crude protein in the diet, and the same behavior was observed in the present database.…”
Section: No3mentioning
confidence: 76%
“…Prior to generating new equations for nitrogen and phosphorus excretion, prediction equations of nitrogen and phosphorus excreted (Geisert et al, 2010;Waldrip et al, 2013;Dong et al, 2014) as proposed by BCNRM (2016), were tested for appropriateness for these database. The tested equations are presented below.…”
Section: Equations Proposed By Bcnrm (2016) Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Dietary crude protein level and N excretion from dairy cattle is primarily affected by N intake; about 70-80% of the N consumed by dairy cows is excreted in manure [62]. The lower N excretion of the corn silage-based system resulted in lower manure N 2 O emissions and less manure N to spread on fields.…”
Section: Item Alfalfa Silage System Corn Silage Systemmentioning
confidence: 99%